2023
DOI: 10.1371/journal.pone.0278594
|View full text |Cite
|
Sign up to set email alerts
|

Web use remains highly regional even in the age of global platform monopolies

Abstract: The Internet, since its inception, has been imagined as a technology that enables information to overcome barriers of language and geography. As a handful of social media platforms now dominate globally, removing most barriers of distribution; this has created unprecedented opportunities for content to gain worldwide traction, regardless of its country of origin. Yet historically with few exceptions, people generally consume content that is from or for their region. Has the Internet or social media really alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A previous study [ 46 ] revealed that COVID-19–themed videos in hard-hit countries used different messaging approaches and gained attention at different times. As the popularity of web content is usually driven by language similarity and geographic proximity [ 47 , 48 ], we cannot draw conclusions about the spread of content in other languages and countries. It is possible that vaccine-related misinformation is moderated more effectively in English than in other languages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study [ 46 ] revealed that COVID-19–themed videos in hard-hit countries used different messaging approaches and gained attention at different times. As the popularity of web content is usually driven by language similarity and geographic proximity [ 47 , 48 ], we cannot draw conclusions about the spread of content in other languages and countries. It is possible that vaccine-related misinformation is moderated more effectively in English than in other languages.…”
Section: Discussionmentioning
confidence: 99%
“…As the popularity of web content is usually driven by language similarity and geographic proximity [47,48], we cannot draw conclusions about the spread of content in other languages and countries. It is possible that vaccine-related misinformation is moderated more effectively in English than in other languages.…”
Section: Limitationsmentioning
confidence: 99%
“…This study attempts to answer Rains’ (2020) call to apply big data and computational techniques to extend the literature on fear appeals. Since web use is blossoming along traditional lines, defined by languages and geographies ( Ng & Taneja, 2019 , 2023 ), beyond English-speaking countries (the United States, Canada, and New Zealand), this study examines YouTube’s message constructs in Taiwan (Traditional Chinese), Brazil (Portuguese), and Russia (Russian) through video transcripts. Employing a supervised machine learning method, this study analyzes phrases and topics related to fear appeals in broader scopes and scales.…”
Section: Literature Reviewmentioning
confidence: 99%